Implementasi Sistem Informasi Layanan Pelanggan Berbasis Web pada Tuku Ramen Menggunakan Model Waterfall - Surya Darmawansyah; Muhammad Abiet Fatwa Kusumadita; Wawan Sugiarto; Yulianti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Information on Tuku Ramen menus, branches, operating hours, packages, frequently asked questions, and reservations was previously distributed across Instagram, Linktree, WhatsApp, and direct communication with administrators. This required customers to access several channels and caused administrators to spend approximately 2–3 hours per day answering repetitive questions. This study aimed to implement a web-based customer service information system as a centralized information and operational data management platform. Data were obtained through service-process observation, an interview with the General Manager, literature review, and application repository inspection. Development used the Waterfall model and was limited to requirements analysis, design, implementation, and testing. The system was modeled using UML and a relational database and implemented with Next.js, TypeScript, Supabase PostgreSQL, Supabase Auth, and Supabase Storage. The public pages provide branch-based menus, packages, locations, operating hours, FAQs, and WhatsApp reservation links. The administrator and owner dashboards support the management of menus, branches, packages, FAQs, images, availability status, and user access. Black-box testing of 15 scenarios showed that all scenarios produced the expected results, representing a 100% functional pass rate. These results demonstrate conformity with the main functional requirements; however, they do not yet demonstrate improvements in efficiency or customer satisfaction because pre–post evaluation and usability testing were not conducted.